PENGUATAN LITERASI EDUKATIF DAN SPIRIT SADAR WISATA BERBASIS “SUSTAINABLE BLUE TOURISM” DI PESISIR SELATAN - Syahputra, Chandra; Febriani, Rina; Reswita, Yefri (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
The enhancement of educational literacy and tourism awareness grounded in Sustainable Blue Tourism represents a strategic necessity in addressing sustainability challenges in coastal regions. This program aims to raise awareness among local communities and tourism stakeholders in Pesisir Selatan about the importance of balancing marine resource management, economic development, and environmental preservation. Through a participatory approach, the initiative incorporates training sessions, interactive discussions, and educational materials to deepen community understanding of the Sustainable Blue Tourism concept. It also instills core tourism values, such as cleanliness, hospitality, and sustainability, in all marine-based tourism activities. The anticipated outcome is the creation of synergy between local communities and stakeholders to support sustainable tourism development that enhances economic well-being without compromising coastal ecosystems. In this way, the program serves as a foundational step toward fostering more inclusive and environmentally conscious tourism practices in Pesisir Selatan.